Polarization analysis of a micro direct methanol fuel cell stack based on Debye-Hückel ionic atmosphere theory. (1st May 2021) - Fang, Shuo; Liu, Yuntao; Zhao, Chunhui; Huang, Lilian; Zhong, Zhi; Wang, Yun
Abstract: In this paper, a micro direct methanol fuel cell (μDMFC) stack model is developed in order to analyze the polarization characteristics. The model employed the Debye-Hückel ionic atmosphere theory to describe the charge conductions and electrochemical kinetics during the polarization coupling. The simulated current-power profiles of the model are verified experimentally. Compared with the μDMFC stack model based on conventional polarization theory, the error of the proposed μDMFC stack model reduces by about 8% at average. For every 10 mol · m −3 increase in cathodic oxygen concentration, the increase in polarization coupling efficiency alone can improve the output power by about 2% on average. The increase of operating temperature from 293 K to 333 K weakens the coupling forces within the μDMFC stack. The analyzing results of dynamic operation show that the polarization coupling causes a voltage peak during unloading. High loading current and unloading speed raise the voltage peak. The energy loss caused by methanol crossover decreases during dynamic operating process. The dynamic energy conversion efficiency of the μDMFC stack is relatively high. The proposed μDMFC stack model solves the polarization coupling problem and makes it possible to analyze the polarization coupling between μDMFC stack and modern microelectronic portable systems. Graphical abstract: Image 1 Highlights: A model is developed to analyze polarization coupling within the μDMFC stack. The model was based on the Debye-Hückel ionic atmosphere theory. The polarization and energy conversion of the μDMFC stack is analyzed. The simulated results correlate well with the experimental results.